Histopathological Analysis of Decellularized Porcine Small Intestinal Submucosa after Treatment of Skin Ulcer. Issue 12 (December 2021) - Kobayashi, Hisashi; Imai, Yasuo; Hirao, Takayuki; Nakao, Ko; Kajinaka, Hayato; Kishi, Kazuo
Abstract : Background: Decellularized porcine small intestinal submucosa (SIS), commercialized as an extracellular matrix rich in cell-inducing substrates and factors, has been clinically applied to treat intractable skin ulcers and has shown therapeutic effects. The SIS reportedly induces cell infiltration and integrates with the ulcer bed after 3–7 days of application. The attached SIS degenerates over time, and the remaining mass appears as slough, below which is granulation tissue that is essential for healing. This study aimed to determine whether the slough should be removed in clinical settings. Methods: Five patients with intractable skin ulcers were included in this case series. Seven days after applying a two-layer fenestrated-type SIS to the ulcer, the removed slough was histopathologically examined. Results: The collagen fibers of the SIS somewhat degenerated, and inflammatory cell infiltration was observed from the ulcer side to the surface side of the SIS. Neovascularization was similarly observed on the ulcer side. The degree of inflammatory cell infiltration decreased from the ulcer side to the surface side, whereas pus (ie, aggregates of neutrophils) was observed on the surface and ulcer edges. Additionally, the removed slough contained regenerative epithelium on the ulcer side of the remaining collagen fibers. Conclusions: After treating intractable skin ulcers using SIS, we recommend removal of the upper surface and ulcer edge of the degenerated SIS or slough to prevent infection and preservation of the lower side of the degenerated SIS to maintain the granulation tissue and regenerative epithelium.